2014
DOI: 10.1080/09712119.2014.980422
|View full text |Cite
|
Sign up to set email alerts
|

Commercial extenders and freezing curves for the preservation of sperm cells of white-tailed deer (Odocoileus virginianus)

Abstract: During the reproductive season of the white-tailed deer, 36 diluted semen samples from deer were evaluated before freezing, and at the time of thawing. The samples were obtained by electro ejaculation from three sedated deer with a mixture of Zoletil ® and xylazine hydrochloride. Samples were diluted with three commercial extenders Biladyl ® , Trilady ® and Bioxcell ® and frozen by applying two freezing curves, the one used for sheep and goat, and the recommended for deer semen. The response variable was the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…This study showed that post-mortem cryopreservation of sperm cells of the Veracruz subspecies of white-tailed deer provided optimal parameters after thawing. On average, the viability (40.00%), progressive motility (35.75%), presence of cytoplasmic droplets (13.50%), and normal morphology (44.50%) are aligned with the consulted literature [7,12,13]. When evaluating the effect of age on the sperm parameters, old bucks (around 4 years) had a higher proportion of sperm cells with normal morphology (p<0.01) and cytoplasmic droplets (p<0.01) compared with younger animals (2 and 3 years old).…”
Section: Resultssupporting
confidence: 73%
“…This study showed that post-mortem cryopreservation of sperm cells of the Veracruz subspecies of white-tailed deer provided optimal parameters after thawing. On average, the viability (40.00%), progressive motility (35.75%), presence of cytoplasmic droplets (13.50%), and normal morphology (44.50%) are aligned with the consulted literature [7,12,13]. When evaluating the effect of age on the sperm parameters, old bucks (around 4 years) had a higher proportion of sperm cells with normal morphology (p<0.01) and cytoplasmic droplets (p<0.01) compared with younger animals (2 and 3 years old).…”
Section: Resultssupporting
confidence: 73%
“…White-tailed deer is a dimorphic species; this dimorphism could be more evident in winter, since this is when the breeding season occurs and the production of testosterone increases (Clemente-Sánchez et al, 2015). Males have well-developed antlers, flared necks, and an accumulation of body fat to maintain themselves during the winter and breeding season (Dostaler, Quillet, Therrien & Côte, 2011;Galindo-Leal & Weber, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…White-tailed deer (Odocoileus virginianus) is one of the most important wildlife species in Mexico due to the number of animals that are hunted annually (Clemente-Sánchez, F., Cessa-Reyes, V., Cortez-Romero, C., Tarango-Arámbula, L. A., & Arenas-Baez, 2015). Established regulations for the harvest of white-tailed deer by institutions in North America usually allow different numbers of animals to be harvested depending upon their sex, having a preference for males (Lindsay & Belant, 2008;Riley et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…La movilidad puede evaluarse por métodos subjetivos y poco fiables o por métodos objetivos, mediante los sistemas CASA (Yániz et al, 2018). El análisis subjetivo de la movilidad considera la movilidad masal (Clemente-Sánchez et al, 2015), que se evalúa en semen no diluido y se valora el número, la densidad y la velocidad del movimiento de las ondas o remolinos que se forman en la superficie de la gota de semen. Cuando no se ven ondas y los espermatozoides no se mueven se asigna un valor cero (categoría inferior), se van asignando valores hasta el valor más elevado (categoría 5, según la escala), donde se observan ondas densas y con movimiento muy rápido.…”
Section: Movilidad Reducida Astenozoospermiaunclassified